The Community-Based Disaster Risk Management (CBDRM) Model as a Strategy for Controlling Rabies in Bali Province - Putu Mira Puspitayani; Syamsul Maarif; Lilik Kurniawan; I Putu Juli Sukariada (International Journal of Education, Vocational and Social Science, 2025)
Rabies is one of the strategic zoonotic diseases caused by rabies virus of the genus Lyssavirus, family Rhabdoviridae, which remains a significant public health threat in Bali Province. Control measures through mass dog vaccination programs, education, and regulatory interventions have been implemented since 2009; however, challenges persist due to resource limitations and suboptimal community participation. This research aims to explore the application of Community-Based Disaster Risk Management (CBDRM) as a strategy for rabies mitigation through a disaster management approach. The research methodology employed a literature review of articles indexed in Scopus and Sinta databases, reports from international organizations, and national and regional policy documents from the period 2015–2025. The findings of this review indicate that CBDRM has the potential to strengthen community capacity, establish cross-sectoral networks, and enhance collective community awareness in rabies prevention. These findings affirm that strengthening community capacity through CBDRM can serve as a sustainable framework for zoonotic disease mitigation in Bali, while simultaneously expanding the disaster management paradigm into the field of veterinary public health.